Effectivity of the Problem-Based Learning Model on Elementary School Students' Critical Thinking Skills in Mathematics Learning - Arif Munandar; Supriadi; Andika Arisetyawan (Journal of Indonesian Primary School, 2026)
Developing critical thinking skills in primary mathematics remains a significant pedagogical challenge, as traditional teacher-centered instruction often fails to stimulate higher-order cognitive processing. While various methodologies have been proposed, empirical confirmation of structured problem-solving frameworks in early mathematics education warrants deeper exploration. This study aims to examine the effect of the Problem-Based Learning (PBL) model on the critical thinking skills of elementary school students in mathematics. Utilizing a quantitative approach with a quasi-experimental design, this research involved fifth-grade students from SKD State Elementary School, divided into an experimental class (grade Va, n = 30, utilizing the PBL model) and a control class (grade Vb, n = 30, utilizing conventional learning). Data were gathered through a dedicated critical thinking ability test and analyzed using descriptive statistics (mean, standard deviation, and percentage of completeness) alongside inferential parametric statistics (independent and paired-sample t-tests). The findings demonstrated that the PBL model exerts a highly positive and statistically significant effect on students' critical thinking skills. The experimental class achieved a substantially higher post-test mean score (M = 90.33) compared to the control class (M = 72.15). Additionally, the experimental group exhibited a smaller standard deviation, indicating a more homogenous and evenly distributed acquisition of critical thinking skills among students. In terms of academic mastery, the experimental class achieved a 92.12% completeness rate, significantly outperforming the control class at 68.43% (p < 0.000). These results suggest that PBL effectively fosters analytical capabilities by immersing students in real-world mathematical inquiry. Consequently, this study underscores the PBL model as a potent pedagogical alternative to mitigate low mathematical reasoning in primary education.